Improving Maternal Health Knowledge through Community-Based Health Promotion on Clean and Healthy Living Behaviors (PHBS) - Ruth H. Dias; Teobaldus A. Arkian; Christina R Nayoan; Noorce Ch. Berek (Jurnal Sipakatau: Inovasi Pengabdian Masyarakat, 2025)
Maternal and child health issues remain a significant challenge in rural areas, primarily due to the lack of knowledge about Clean and Healthy Living Behavior (PHBS). This community service activity aimed to improve the knowledge and awareness of housewives in Tetaf Village, South Central Timor Regency, regarding the importance of implementing PHBS in daily life. The method used was interactive health education combining participatory lectures and group discussions, evaluated through pre-test and post-test instruments. The activity was held on June 5, 2025, at the Posyandu of the Tetaf Village Office and involved 20 housewives as participants. The materials were delivered using contextual and easy-to-understand visual aids adapted to local conditions. The results showed a significant improvement in participants' knowledge. The average pre-test score was 59, which increased to 95 on the post-test. In addition to this cognitive gain, participants also demonstrated high enthusiasm, as seen in their active involvement in the discussion sessions and their expressed commitment to adopting PHBS practices at home. The interactive approach enabled effective two-way communication between facilitators and participants, creating a more meaningful learning experience. These findings indicate that interactive and context-sensitive community-based health education is highly effective in enhancing health literacy, particularly among housewives. It is expected that this initiative can serve as a sustainable educational model for similar rural areas to support broader and more equitable health promotion efforts across Indonesia.